Maxillary anterior root resorption in Class II/I malocclusion patients post fixed orthodontic treatment - Fransiska Rima Tallo; Ida Bagus Narmada; I. G. A. Wahju Ardani (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Previous studies on root resorption were reviewed by panoramic radiographs. Cone-beam computed tomography (CBCT) showed that 41.5% of teeth experienced resorption when panoramically examinated, while 68% of teeth experienced resorption when the examination method used was CBCT. Root resorption occurs in the maxillary central incisor (as much as 74%) and in the maxillary lateral incisor (as much as 82%). The maxillary canines have the most resorption, followed by the lateral maxillary incisors. Purpose: The aim of this study was to determine the differences of apical resorption in anterior maxillary teeth before and after orthodontic treatment in skeletal Class I/II cases of extraction. Methods: Samples from this study were the results of panoramic photographs of 50 patients treated by fixed orthodontic appliances at the Dental and Oral Hospital Airlangga University. These were selected according to the sample criteria. The evaluation method consists of measuring root and crown lengths with a digital application (RadiAnt DICOM Viewer). Subsequently, the measurements were evaluated using CBCT images. Results: The data were statistically analysed using normality tests with Shapiro–Wilk and Kolmogorov–Smirnov tests. Based on the results of paired sample tests, it was found that every treatment group had significant differences in the average length of the crowns and roots, with a result of p=0.000 (p<0.05). Conclusion: The use of CBCT is considered quite effective and accurate in evaluating root resorption compared to panoramic photographs.